Home care: o que as seguradoras devem e os segurados podem? - Seyfferth, Walter Carlos (Universidade do Vale do Rio dos Sinos, 2018)
The work analyzes the obrigational limits between insurance companies and insured parties in health insurance contracts, especially, in a relation with the judicial interpretation of legal transaction carried out, which the knowledge has understood to extend the contractual effects to the coverage of Home Care treatment in general, even though there are clauses expressly blindfolded such provision, which ends up significantly encumbering the insurer, especially when viewing the situation of the insured’s home hospitalization rather than the basic care of home care, which reproduces a legal uncertaintly about the actual design of the institutes. To realize this research were used the phenomenological-hermeneutic research method whose execution has analytic-descriptive forays. Based on the Critical Theory of Law, it was observed the configuration of a dogmatic dispute due to the lack of regulation of home care by National Health Agency, resulting in judicial decisions that are contrary to the social function and economic order of the contract.
Keywords: Assistência domiciliar; Assistência hospitalar; Contratos; Home care; Internação domiciliar; Limites; Seguradora; Segurado; Home assistence; Hospital care; Contracts; Home care; Home hospitalization; Limits; Insurance company; Insured; ACCNPQ::Ciências Sociais Aplicadas::Direito